2011
DOI: 10.1136/jfprhc.2010.0014
|View full text |Cite
|
Sign up to set email alerts
|

Views of contraceptive service delivery to young people in the UK: a systematic review and thematic synthesis

Abstract: Background and methodology Despite widespread availability of contraceptives and increasing service provision in the UK, rates of teenage pregnancy remain a concern. It has been suggested that young people face particular obstacles in accessing services, leading to a need for specialist provision. This systematic review examined the literature reporting views of service providers and young people. Data were synthesised in order to develop key themes to inform the development of contraceptive services for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 58 publications
2
15
0
1
Order By: Relevance
“…The review excludes women's reasons for abortion,22 23 abortion in adolescence,24 25 late-stage abortion,5 access issues in relation to safe abortion,20 women in developing countries3 26 or countries where abortion is legally restricted27 28 as the contextual social and legal access issues were likely to vary too much between settings.…”
Section: Methodsmentioning
confidence: 99%
“…The review excludes women's reasons for abortion,22 23 abortion in adolescence,24 25 late-stage abortion,5 access issues in relation to safe abortion,20 women in developing countries3 26 or countries where abortion is legally restricted27 28 as the contextual social and legal access issues were likely to vary too much between settings.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that the openness of young people in medical consultations could be improved were doctors to take the time stress the confidential nature of the encounter. Indeed a systematic review of contraceptive service delivery to young people in the UK based on 59 articles concluded that the most dominant concern for young people was that anonymity and confidentiality be maintained (Baxter, Blank, Guillaume, Squires, & Payne, 2011); these authors stressed the importance of young people being reassured about this. These studies, as indicated, related to young people in general and not those in state care, but the implications of information being shared between health professionals are greater for young people in care who interface with multiple professionals and who may well be deterred from availing of the sexual health services as required.…”
Section: Discussionmentioning
confidence: 99%
“…Young people may find it hard to access clinic services because of their concerns about privacy and confidentiality and fears about staff being critical or unfriendly. 35 The convenience of clinic locations and opening hours is particularly important for young people, who may face restrictions on where they can go and when. 35 Sexual health promotion forms a core component of care in sexual health clinics (e.g.…”
Section: Sexual Health Promotion In Clinic and Community Settingsmentioning
confidence: 99%
“…35 The convenience of clinic locations and opening hours is particularly important for young people, who may face restrictions on where they can go and when. 35 Sexual health promotion forms a core component of care in sexual health clinics (e.g. as a part of a health advisor role), but the quality and intensity of advice or support is variable.…”
Section: Sexual Health Promotion In Clinic and Community Settingsmentioning
confidence: 99%